1976
DOI: 10.1016/0012-821x(76)90119-9
|View full text |Cite
|
Sign up to set email alerts
|

The case for an unfractionated244Pu/238U ratio in high-temperature condensates

Abstract: The coarse-g~ained, Ca-rich inclusions in the AUende meteorite are the highest-temperature condensates from the cooling solar nebula and, as such, the oldest solid objects in the solar system. All refractory elements with condensalion points above the accretion temperature of the inclusions whose eoneentrarions in them have been measured are seen to be present in the inclusions in unfractionated proportion to one another relative to C1 ehondrites when data ate averaged for a large number of inclusions. Observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…-The concentra tions of U and Th are listed in Table 4. The value of U is the mean concen tration from nine coarse-grained Allende inclusions (Ganapathy and Grossman, 1976) and is consistent with other results (Wanke et al, 1974). The concentration of Th is obtained by assuming the cosmic abundance ratio of Th/U n 0 4.…”
Section: U Th and Heat Productionsupporting
confidence: 91%
See 1 more Smart Citation
“…-The concentra tions of U and Th are listed in Table 4. The value of U is the mean concen tration from nine coarse-grained Allende inclusions (Ganapathy and Grossman, 1976) and is consistent with other results (Wanke et al, 1974). The concentration of Th is obtained by assuming the cosmic abundance ratio of Th/U n 0 4.…”
Section: U Th and Heat Productionsupporting
confidence: 91%
“…The enrichment factor for refractories between Allende inclusions and Cl chondrites is about 20 (Wanke et al, 1974;Martin, 1975, Ganapathy andGrossman, 1976). The only elements of these groups that we consider in detail are U and Th due to their significance as long-lived heat sources.…”
Section: U Th and Heat Productionmentioning
confidence: 96%
“…The aar~~/Zs%u abundance ratio is found from decay pr0duct.s of 241Pu. Ganapathy and Grossman (1976) proposed that the solar system *4nPu/*JsU a,bundance ra,tio be determined from coarse-grained Ca-Al-rich inclusions from Allende since they found that in ten such coarsegrained inclusions the average relative abundance of 21 refractory elements was unfractionated with respect to Cl chrondrite abundances. The advantage of these inclusions is that absolute concentra,tions of these elements are some 18 times greater than t,he Cl abundances.…”
Section: I) Re/osmentioning
confidence: 99%
“…This interpretation was supported by Lawrence Grossman (1973) and his colleagues (Grossman and Clark, 1973;Grossman and Larimer, 1974;Grossman and Olsen, 1974;Olsen and Grossman, 1974;Grossman, 1975;Ganapathy and Grossman, 1976;Grossman and Steele, 1976).…”
Section: High-temperature Condensationmentioning
confidence: 88%
“…The major opposition to lunar-terrestrial similarity came from the Anders group, which favored coaccretion after fractionation in the solar nebula; they argued that the moon was formed in a circumterrestrial orbit from material that had condensed at higher temperatures than the Earth (Ganapathy and Anders, 1974). Another version of the coaccretion theory, developed by Ruskol (1971aRuskol ( , 1971b attributed compositional differences to processing of incoming planetesimals by collisions with the circumterrestrial swarm over a long period of time (10 8 yrs); volatiles would be removed from the outer edge by the solar wind, silicates would be broken up and remain in the swarm, while iron would pass through and be accreted by the growing Earth.…”
Section: A All Theories Are Refuted By the Datamentioning
confidence: 99%